Bauran Pemasaran Pupuk Organik Bokashi Kotaku pada PT. Karya Pak Oles Tokcer Kota Denpasar, Provinsi Bali - LELY RATNA SIHOMBING; I MADE SUDARMA; UDAYANI WIJAYANTI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2013)
ABSTRACT The marketing mix is a combination of four variables which constitute the core of the company's marketing system, consisting of product, price, place / distribution and promotion channels. This study aims to determine the marketing mix done by. PT. Karya Pak Oles Tokcer and constraints faced in marketing their products. Locations were selected by purposive sampling. The types of data collected included primary data and sekunde. Data collected by the method of observation, in-depth interviews and documentary study. Data were analyzed by descriptive kualitatf. Based on the survey results revealed that the marketing mix done by. PT. Karya Pak Oles Tokcer the product is, the company provides two different types of packaging in marketing their products to make it look more attractive in the eyes of consumers. For this type of regular use plastic packaging for the type of packaging sacks Kampil use. Bokashi fertilizer selling prices are determined based on a calculation of marketed raw material, labor, production, operating costs and other costs. Based on place / distribution channel, my town Bokashi fertilizer marketed through direct marketing distribution channels and indirectly. Promotional products through direct marketing activities (counter sales), sales promotion (rebates and bonuses) and advertising (brochures, newspapers, and radio from the company itself). Constraints faced by the company consists of internal and external constraints. Internal constraints in terms of the promotion of a less effective. External constraints in terms of competitors similar products. Keyword : Marketing Mix Pupuk Bokashi Kotaku.